Poverty focussed rural good governance in Asian Commonwealth countries : Commonwealth Secretariat-CIRDAP Workshop on Sharing Successful Experiences on Poverty Focused Rural Good Governance in Asian Commonwealth Countries : 27-31 May, 2006, CIRDAP, Dhaka, Bangladesh - Sudhakar Rao, B. (CIRDAP training series ;, 2008)
Papers presented at the workshop; with reference to South and Southeast Asian countries; workshop organized by Commonwealth Secretariat and Center on Integrated Rural Development for Asia and the Pacific.